Toxic anterior-segment syndrome (TASS) - Cetinkaya, Servet (Dove Medical Press, 2014)
PURPOSE: To evaluate the clinical findings and courses of five patients who developed toxic anterior-segment syndrome (TASS) after cataract surgery and investigate the cause. MATERIALS AND METHODS: In May 2010, on the same day, ten patients were operated on by the same surgeon. Five of these patients developed TASS postoperatively. RESULTS: Patients had blurred-vision complaints on the first day after the operation, but no pain. They had different degrees of diffuse corneal edema, anterior-chamber reaction, fibrin, hypopyon, iris atrophies, and dilated pupils. Their vision decreased significantly, and their intraocular pressures increased. Both anti-inflammatory and antiglaucomatous therapies were commenced. Corneal edema and inflammation resolved in three cases; however, penetrating keratoplasty was needed for two cases and additional trabeculectomy was needed for one case. Although full investigations were undertaken at all steps, we could not find the causative agent. CONCLUSION: TASS is a preventable complication of anterior-segment surgery. Recognition of TASS, differentiating it from endophthalmitis, and starting treatment immediately is important. Controlling all steps in surgery, cleaning and sterilization of the instruments, and training nurses and other operation teams will help us in the prevention of TASS.